2021
DOI: 10.1021/acs.jpclett.1c03515
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-Up Synthesis of 1,1-Ethenediol (H2CC(OH)2)─The Simplest Unsaturated Geminal Diol─In Interstellar Analogue Ices

Abstract: Because of their nucleophilic character and high reactivity, enolsreaction intermediates carrying a hydroxyl group connected to a carbon–carbon double bondplay a key role in the formation of complex organic molecules in astrobiology and biochemistry. Here, we report the first bottom-up preparation of 1,1-ethenediol (H2CC­(OH)2)the simplest unsaturated geminal enol of acetic acid (CH3COOH) and potential precursor for the formation of glycinein interstellar analogue ices of carbon dioxide and methane process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…3). In addition, keto-enol tautomerization reaction can occur in the irradiated ices as shown previously by Kleimeier et al 16,61 and thus their enol products may also be detected at 10.49 eV. Thereafter, the photon energy was reduced to 9.70 eV; at this energy, isomers/conformers 1b, 2a, and 3a–3c cannot be ionized (Fig.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…3). In addition, keto-enol tautomerization reaction can occur in the irradiated ices as shown previously by Kleimeier et al 16,61 and thus their enol products may also be detected at 10.49 eV. Thereafter, the photon energy was reduced to 9.70 eV; at this energy, isomers/conformers 1b, 2a, and 3a–3c cannot be ionized (Fig.…”
Section: Resultssupporting
confidence: 57%
“…58,59 Laboratory studies of interstellar analog ices have demonstrated the formation of enols – the thermodynamically less stable tautomers of aldehydes and ketones – in astrochemically relevant ice mixtures after the exposure of energetic electrons; these low temperature experiments detected vinyl alcohol (C 2 H 3 OH), 16,20 1-propenol (CH 3 CHCH(OH)), 20 2-hydroxyacrylic acid (CH 2 (COH)COOH), 37 ethynol (HCCOH), 60 1,2-ethenediol (HOCHCHOH) 45 and 1,1-ethenediol (H 2 CC(OH) 2 ), 61 suggesting that enols should be ubiquitous in the interstellar medium. 16,45,61 However, only vinyl alcohol 62 and 1,2-ethenediol 63 have been detected in deep space so far. In organic synthesis, simple enols are usually regarded as short-lived species, 64 however, in enzymatic mechanisms, they are long-lived species playing key roles as intermediates.…”
Section: Introductionmentioning
confidence: 96%
“…24,25 Such molecules formed in the interstellar ices can be eventually incorporated into comets and may be delivered to planets such as Earth. 26 Therefore, our results further contribute to the understanding of the formation pathways of sulfur-bearing molecules detected in the ISM, shed light on the prebiotic synthesis of proteins, 14 and thus expand our knowledge on the evolution of biorelevant molecules in the universe.…”
Section: H Co Hco +mentioning
confidence: 66%
“…Table S2 summarizes the IR absorption features of the pristine ice and new absorption features after irradiation. The formyl radical (HĊO) is identified from the ν 3 fundamental (CO stretch) at 1840 cm –1 in irradiated ices. , The feature at 2045 cm –1 was present prior to the irradiation and was assigned to the overtone mode (2ν 2 ) of hydrogen sulfide; however, this peak increased after irradiation, suggesting that it is also associated with the formed products. Ferrante et al reported the absorption features of OCS (ν 3 ) at 2047 and 2054 cm –1 in CO–OCS ice and CO 2 –OCS ice at 11 K, respectively .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation